3D hierarchical defect-rich NiMo3S4 nanosheet arrays grown on carbon textiles for high-performance sodium-ion batteries and hydrogen evolution reaction. (July 2018) - Kong, Dezhi; Wang, Ye; Lim, Yew Von; Huang, Shaozhuan; Zhang, Jun; Liu, Bo; Chen, Tupei; Yang, Hui Ying
Abstract: A hierarchical hybrid nanostructure composed of NiMo3 S4 nanosheet arrays with abundant exposed edges on flexible carbon textiles (denoted as NiMo3 S4 /CTs) has been designed and synthesized for sodium ion batteries (SIBs) and electrocatalytic hydrogen evolution reaction (HER). The novel NiMo3 S4 nanostructure, formed by incorporating Ni 2+ into Mo-S lattice, shows plenty of substantial defects and active sites, which are favorable for the improvement of the overall electrochemical performances for both SIBs and HER. When evaluated as the anode of SIBs, the NiMo3 S4 /CT electrode delivers a high specific capacity of 480 mA h g −1 at a current density of 0.12 A g −1 and a high Coulombic efficiency of 100%. Moreover, the NiMo3 S4 /CT electrode shows an excellent long-term cycling performance with a high reversible capacity of 302 mA h g −1 after 1000 cycles at 0.48 A g −1, showing a high capacity retention of 73.9%. Furthermore, as a HER catalyst, the NiMo3 S4 /CT hybrid nanostructure exhibits a low onset over-potential of 0.124 V, a small Tafel slope of 46.2 mV dec −1 as well as an excellent long-term stability, which are among the best values of current noble-metal-free electrocatalysts. These results may open up a new route to introduce more active defect sites to enhance the electrochemical performance of metal sulfides by incorporation of metal elements. Graphical abstract: 3D hierarchical NiMo3 S4 nanosheet arrays with abundant exposed edges tightly anchored on the flexible carbon textiles has been synthesized by a simple one-step hydrothermal approach and further investigated as anodes for both sodium-ion batteries and hydrogen evolution reaction.fx1 Highlights: 3D hierarchical defect-rich NiMo3 S4 nanosheet arrays tightly anchored on flexible carbon textiles were synthesized. The incorporation of Ni 2+ offer substantial defect sites and increasing the interlayer spacing of NiMo3 S4 nanoflakes. The novel NiMo3 S4 /CTs electrode exhibits enhanced performance in both sodium-ion storage and hydrogen evolution reaction.